2004
DOI: 10.1159/000077461
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of DNA double strand break repair and chromosome aberration formation

Abstract: It is widely accepted that unrepaired or misrepaired DNA double strand breaks (DSBs) lead to the formation of chromosome aberrations. DSBs induced in the DNA of higher eukaryotes by endogenous processes or exogenous agents can in principle be repaired either by non-homologous endjoining (NHEJ), or homology directed repair (HDR). The basis on which the selection of the DSB repair pathway is made remains unknown but may depend on the inducing agent, or process. Evaluation of the relative contribution of NHEJ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
264
4
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(280 citation statements)
references
References 37 publications
11
264
4
1
Order By: Relevance
“…Activation of p21 by delayed chromosome breaks Micronuclei are eliminated through cell divisions (Fenech, 1993;Iliakis et al, 2004). In our present study, DNA damage was introduced at the zygotic stage, but the frequency of micronuclei increased in later stages of embryogenesis, suggesting generation of new chromosome breaks.…”
Section: Transcriptional Activation Of Genes During Early Mouse Embrymentioning
confidence: 52%
“…Activation of p21 by delayed chromosome breaks Micronuclei are eliminated through cell divisions (Fenech, 1993;Iliakis et al, 2004). In our present study, DNA damage was introduced at the zygotic stage, but the frequency of micronuclei increased in later stages of embryogenesis, suggesting generation of new chromosome breaks.…”
Section: Transcriptional Activation Of Genes During Early Mouse Embrymentioning
confidence: 52%
“…However, this microhomology driven backup system appears to be quite error-prone, as chromosomal translocations have frequently been found to contain microhomologies at the junctions. The existence of backup end-joining pathways may explain why chromosomal translocations have been found regularly in cells with defects in NHEJ components, although this process obviously requires joining of DNA ends (Iliakis et al, 2004;Burma et al, 2006).…”
Section: Alternative End-joining Pathwaysmentioning
confidence: 99%
“…Different studies found that tobacco smoke condensate induces various genetic aberrations, including gene mutations, chromosome aberrations, micronuclei (MN), sister chromatid exchanges, DNA strand breaks, and oxidative DNA adducts, in different tissues (3). Unrepaired or misrepaired DNA double-strand breaks, that are induced or occur spontaneously, are considered to be the most important lesion responsible for the production of aberrations (4,5). Tobacco smoke is a mixture of more than 5000 toxic and carcinogenic chemicals (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%